Hong Kong and Singapore exchanges confront high frequency trading. Issue 1 (1st January 2017) - Meyer, David R.; Guernsey, George
Abstract: The Hong Kong (HKEx) and Singapore (SGX) exchanges remain conflicted about high frequency trading (HFT), reflecting the environment of private and public sector actors in which the HKEx and SGX operate. Neither exchange has resolved these conflicts, leaving the HFT controversy simmering and limiting the amounts of such trading occurring on their exchanges. Competitor exchanges in Asia, however, are more supportive of HFT. With the aid of technology providers which enable HFT, the HKEx and SGX significantly improved their trading infrastructures. At the same time, these providers developed data centres at other exchanges and built fibre-optic connections which permit low-latency trading across Asia. Traders in Hong Kong and Singapore access these exchanges, potentially undermining the HKEx and SGX.